(untitled) (Vietnam Journal of Community Medicine, 2022)
Purposes: This study aimed to compare knowledge and practices of male and female towards hands washing and masks wearing during COVID‐19 (coronavirus disease 2019) pandemic in Thong Nhat hospital Materials and method: We conducted a cross-sectional study among patients who come to outpatient care at Thong Nhat Hospital, Ho Chi Minh City from May 2020 to July 2020. Researchers interviewed patients directly using prepared questionnaires. Results: A total of 1,555 patients were included into the study with 804 males (51.7%) and 751 females (48.3%). There were significantly different between the male and female groups about age, qualification and employment status (p<0.001). More than 80 percent of respondents in both groups frequently wash their hands with hand sanitizer or soap, 83.2% in male groups and 85.4% in femal groups (p = 0.230). Nearly all of the patients in both groups wore masks when going out in the last month (98.9% with 98.1%, p = 0.224). Conclusion: The results showed that there are not much gender differences in knowledge and practices for hand washing and mask wearing during COVID-19 pandemic.